Hematological profile of normal pregnant women in Lagos, Nigeria - Akinbami AA; Ajibola SO; Rabiu KA; Adewunmi AA; Dosunmu AO; Adediran A; Osunkalu VO; Osikomaiya BI; Ismail KA (Dove Medical Press, 2013)
Akinsegun A Akinbami,1 Sarah O Ajibola,2 Kabiru A Rabiu,3 Adeniyi A Adewunmi,3 Adedoyin O Dosunmu,1 Adewumi Adediran,4 Vincent O Osunkalu,4 Bodunrin I Osikomaiya,5 Kamal A Ismail,51Department of Haematology and Blood Transfusion, Lagos State University, College of Medicine, 2Department of Haematology and Blood, Lagos University Teaching Hospital, 3Department of Obstetrics and Gynaecology, Lagos State University, College of Medicine, 4Department of Haematology and Blood, Faculty of Clinical Sciences, College of Medicine, University of Lagos, 5Department of Haematology and Blood Transfusion, Lagos State University Teaching Hospital, Lagos, NigeriaBackground: Hematological profile is considered one of the factors affecting pregnancy and its outcome. Anemia is the most common hematological problem in pregnancy, followed by thrombocytopenia. Leukocytosis is almost always associated with pregnancy. The study reported here was designed to evaluate the overall mean values of seven major hematological parameters and their mean values at different trimesters of pregnancy.Subjects and methods: This examination was a cross-sectional study of 274 pregnant women who registered to attend the Lagos University Teaching Hospital or Lagos State University Teaching Hospital antenatal clinics between their first and third trimester. Blood (4.5 mL) was collected from each participant into a tube containing the anticoagulant ethylenediaminetetraacetic acid (EDTA). A full blood count was performed on each sample and the results were analyzed.Results: Overall, the values obtained were (mean ± standard deviation [SD]): hematocrit level, 30.16% ± 5.55%; hemoglobin concentration, 10.94 ± 1.86 g/dL; white blood cells, 7.81 ± 2.34 × 109; platelets, 228.29 ± 65.6 × 109; cell volume 78.30 ± 5.70 fL, corpuscular hemoglobin, 28.57 ± 2.48 pg; and corpuscular hemoglobin concentration, 36.45 ± 1.10 g/dL. When grouped by trimester, the mean ± SD value of packed cell volume at first trimester was 32.07% ± 6.80%; of second trimester, 29.76% ± 5.21%; and of third, 33.04% ± 3.88%. The mean ± SD hemoglobin concentration values were 11.59 ± 2.35 g/dL, 10.81 ± 1.72 g/dL, and 10.38 ± 1.27 g/dL for women in their first, second, and third trimester, respectively. Mean ± SD white blood cell concentration for first, second, and third trimesters were 7.31 ± 2.38 × 109, 7.88 ± 2.33 × 109, and 8.37 ± 2.15 × 109, respectively, while the mean ± SD platelet values for first, second, and third trimesters were 231.50 ± 79.10 × 109, 227.57 ± 63 × 109, and 200.82 ± 94.42 × 109, respectively. A statistically significant relationship was found to exist between packed cell volume and white blood cell count with increase in gestational age (P = 0.010 and 0.001, respectively). However, there was no statistically significant association between platelet count and increase in gestational age (P = 0.296).Conclusion: These findings reinforce the need for supplementation and provide additional information on hematological reference values in pregnancy in Nigeria.Keywords: anemia, thrombocytopenia, hematology, normal pregnancy, trimester